(untitled) (Khairulummah, 2022)
There is no doubt that every newly emerging country must face many problems and difficulties that lead to the delay in its prosperity and development, and that stability does not come to it overnight, but rather it needs a lot of time and sacrifices in order to reach the degree of stability and prosperity. The Umayyad Islamic state in Andalusia, which went through such conditions until it reached the height of its stability, due to the great sacrifices that Muslims made for this, the political wisdom enjoyed by the Muslim caliphs, and the good administrative measure they worked with, and in this article the researcher will stand on The stages that the Andalusian state went through until it reached stability in all its political, economic, social and other forms.